If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + 3m(m + -8) = 1 Reorder the terms: 2m + 3m(-8 + m) = 1 2m + (-8 * 3m + m * 3m) = 1 2m + (-24m + 3m2) = 1 Combine like terms: 2m + -24m = -22m -22m + 3m2 = 1 Solving -22m + 3m2 = 1 Solving for variable 'm'. Reorder the terms: -1 + -22m + 3m2 = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + -22m + 3m2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -0.3333333333 + -7.333333333m + m2 = 0 Move the constant term to the right: Add '0.3333333333' to each side of the equation. -0.3333333333 + -7.333333333m + 0.3333333333 + m2 = 0 + 0.3333333333 Reorder the terms: -0.3333333333 + 0.3333333333 + -7.333333333m + m2 = 0 + 0.3333333333 Combine like terms: -0.3333333333 + 0.3333333333 = 0.0000000000 0.0000000000 + -7.333333333m + m2 = 0 + 0.3333333333 -7.333333333m + m2 = 0 + 0.3333333333 Combine like terms: 0 + 0.3333333333 = 0.3333333333 -7.333333333m + m2 = 0.3333333333 The m term is -7.333333333m. Take half its coefficient (-3.666666667). Square it (13.44444445) and add it to both sides. Add '13.44444445' to each side of the equation. -7.333333333m + 13.44444445 + m2 = 0.3333333333 + 13.44444445 Reorder the terms: 13.44444445 + -7.333333333m + m2 = 0.3333333333 + 13.44444445 Combine like terms: 0.3333333333 + 13.44444445 = 13.7777777833 13.44444445 + -7.333333333m + m2 = 13.7777777833 Factor a perfect square on the left side: (m + -3.666666667)(m + -3.666666667) = 13.7777777833 Calculate the square root of the right side: 3.711842909 Break this problem into two subproblems by setting (m + -3.666666667) equal to 3.711842909 and -3.711842909.Subproblem 1
m + -3.666666667 = 3.711842909 Simplifying m + -3.666666667 = 3.711842909 Reorder the terms: -3.666666667 + m = 3.711842909 Solving -3.666666667 + m = 3.711842909 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3.666666667' to each side of the equation. -3.666666667 + 3.666666667 + m = 3.711842909 + 3.666666667 Combine like terms: -3.666666667 + 3.666666667 = 0.000000000 0.000000000 + m = 3.711842909 + 3.666666667 m = 3.711842909 + 3.666666667 Combine like terms: 3.711842909 + 3.666666667 = 7.378509576 m = 7.378509576 Simplifying m = 7.378509576Subproblem 2
m + -3.666666667 = -3.711842909 Simplifying m + -3.666666667 = -3.711842909 Reorder the terms: -3.666666667 + m = -3.711842909 Solving -3.666666667 + m = -3.711842909 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3.666666667' to each side of the equation. -3.666666667 + 3.666666667 + m = -3.711842909 + 3.666666667 Combine like terms: -3.666666667 + 3.666666667 = 0.000000000 0.000000000 + m = -3.711842909 + 3.666666667 m = -3.711842909 + 3.666666667 Combine like terms: -3.711842909 + 3.666666667 = -0.045176242 m = -0.045176242 Simplifying m = -0.045176242Solution
The solution to the problem is based on the solutions from the subproblems. m = {7.378509576, -0.045176242}
| 3t^2+4t+21=0 | | 6-3-4=2+x | | 2x*2+8*2=3x*2+2x | | .05(.3m+35n)-.8(-.09n-22)= | | 2(x+3)+x=4(-3) | | -5-r=10 | | f(x)=x^2+6x+18 | | 8x+3(2-3x)=25 | | 194-2x=43x+19 | | 24x^2+24x=0 | | 27+(4x-30)+(3x-10)+x=360 | | 4(1)-5y=9 | | a^3+7a^2+12a+24= | | 6x^2-9x-105=0 | | 15=200 | | -3x+4y=21 | | -10x+6y=-2(3-y) | | 65-131=11(x-1) | | x-11=-3-20 | | -2x=-6y+9 | | 11x-10x=8x+5 | | x+3=-28+10 | | 4a^2+2.25a+1=0 | | (x+8)(x)(x-2)=96 | | 3x/2+6x/5=5+x/5 | | 5z-z=5-37 | | x-42=48 | | 6v^2-9v-60=0 | | (x+4)(x)(x-2)=96 | | -20x=-10 | | 4x^2-24x+32= | | 2q+b=c |